Is Flow Possible in the Emergency Remote Teaching Foreign Language Classroom? - Jean-Marc Dewaele; Alfaf Albakistani; Iman Kamal Ahmed (MDPI AG, 2022)
The present study focuses on the experience of flow among 168 Arab and Kurdish English Foreign Language (EFL) learners in both in-person and emergency remote teaching (ERT) classes. Statistical analyses of questionnaire data revealed that learners did experience flow in their ERT classes but for a significantly shorter time than in the pre-pandemic in-person classes. Those who experienced flow in in-person classes were also more likely to experience it in ERT classes. In the in-person classes, the proportion of time in flow was linked to age, self-rated proficiency, attitudes toward English, attitudes toward the teacher, and the teacher frequency of use of English. In contrast, in ERT classes, the proportion of time in flow was only linked to attitude toward the teacher. This is interpreted as evidence that the ERT does not just cause physical and social isolation but also mental isolation.